The Relation between the New Clinical Parameter "Oscillatory Gap" and Carotid Intima Media Thickness as a Marker for Atherosclerosis - Mohammad El Tahlawi; Abdelrahman Elmurr; Mohammad Gouda (Archives of Clinical Hypertension - Peertechz Publications, 2017)
Introduction: Carotid intima media thickness (CIMT) is an early ultrasonographic marker of atherosclerosis. A new clinical marker "oscillatory gap" (OG) was found to increase with advanced atherosclerosis. Aim: We aim to find a relationship between this clinical marker, OG, and a known ultrasonographic marker of atherosclerosis as CIMT. Patients and Methods: Patients who underwent ultrasonographic assessment of CIMT in our center due to different indications were enrolled. The blood pressure (BP) of all cases was measured. The oscillatory systolic BP (OSBP) was defi ned as the point at which the mercury starts to oscillate. The auscultatory systolic BP (AUSBP) was defi ned as fi rst KorotKoff sound. The difference between OSBP and AUSBP was calculated for OG. The correlation between OG and the CIMT was statistically calculated. Results: The study comprised 85 patients with mean age 61.7±12.9 years. They included 47 patients with signifi cant OG (≥ 10 mmHg) and 38 patients with non-signifi cant gap (<10 mmHg). There was a signifi cant correlation between OG and CIMT (p<0.05). There was a highly signifi cant difference between both groups regarding CIMT (p=0.000). A cutoff value of 10mmHg for OG could predict increased CIMT≥8mm with a sensitivity of 92% and specifi city of 85%. Conclusion: OG could be a marker of advanced atherosclerosis. It correlates signifi cantly with CIMT. A cutoff value of 10mmHg of OG can predict CIMT≥8mm.